An Agreement between the Aga Khan Foundation (Bangladesh) and Institute of Educational Development (IED), BRAC University (2008) - Aga Khan Foundation; Institute of Educational Development, BRAC University (Aga Khan Foundation and Institute of Educational Development (IED), BRAC University, 2013)
An agreement made as of the first day of April 2008 between the Aga Khan foundation (Bangladesh) having its office at SW(F) 3B, Road no. 2. Gulshan 1, P.O. Box 6025, Dhaka 1212, Bangladesh. being a branch of Aga Khan Foundation, a charitable organization incorporated in Geneva, Switzerland (the 'Grantor') [ Of the one part ] and BRAC- Institute of Educational Development (IED), a charitable society incorporated under the laws of Bangladesh and having its head office at 113/A road 2, Niketon, Gulshan 1, Dhaka- 1212, Bangladesh (Of the other part)